PILAR PENYANGGA KEMAJUAN CHINA AN PELUANG MENJADI NEGARA ADI KUASA - Raharjo, Sandhy Nur Ikfal (Jurnal Penelitian Politik, 2025)
After the declaration ofeconomic reform in 1978 China has transformed to be one of the bigpowers in the world Thisfact then leads curiosity on the determinantfactors ofChina s miracle This essay summarizes John and Doris Naisbitt s research based book on 8 pillars ofChina s new society that consist ofemancipation ofthe mind balancing top down and bottom up framing theforest and letting the trees grow crossing the river byfeeling the stones artistic and intellectualferment joining the world freedom andfairness andfrom Olympic medals to Nobel prizes This essay also tries to grasp China s possibility to be the solely superpower and leaving the U S behind